Problemas de programação geométrica signomial via otimização DC - Borges, Clarissa Pessoa (2014)
In this work an approach theory of geometrical problems and programming optimization theory Convex Difference Function (DC) is shown which is made of a class of geometric programming problems, known as Signomiais problems can be written as the difference convex functions and further, a DC problem can be written as CDC which is the canonical form of the problem DC. The advantage of writing in the form CDC is that one can find a global solution to this problem. The problem is solved by reference to Articles Nenad [20], Maranas [17] e Dembo [5].